PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DI CV PRIMA NUSANTARA KRUENG GEUKUEH: PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DI CV PRIMA NUSANTARA KRUENG GEUKUEH - Dedi Miswar; Abubakar Debet; Jumadi; Siraj; Islami Fatwa (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the implementation of the Occupational Safety and Health Management System (SMK3) at CV. Prima Nusantara as an effort to prevent workplace accidents and improve employee safety. The research employed a qualitative descriptive approach using interviews, observations, and documentation as data collection techniques. The findings reveal that the implementation of SMK3 at CV. Prima Nusantara has been carried out effectively, as evidenced by safety policies, regular training, and the provision of personal protective equipment for employees. However, some challenges remain, including limited worker understanding of safety procedures and insufficient supervision in field practices. These results indicate that while SMK3 implementation is relatively successful in reducing potential accident risks, continuous efforts are still needed to strengthen workers’ awareness and compliance. This research contributes by providing practical insights into SMK3 implementation strategies within medium-scale enterprises, which can serve as a reference for vocational education institutions and practitioners in fostering a stronger safety culture in the workplace.